Characteristics and origin of carbon isotopes of n-alkanes in crude oils from the western Pearl River Mouth Basin, South China sea. (November 2015) - Cheng, P.; Xiao, X.M.; Gai, H.F.; Li, T.F.; Zhang, Y.Z.; Huang, B.J.; Wilkins, R.W.T.
Abstract: The quantitative characterization of carbon isotopes of n-alkanes is commonly carried out in organic geochemical studies. Possible controls on carbon isotopes include source organic matter, maturity, fractionation during oil expulsion and migration, and the mixing of different oils. In this study of the origin of crude oils in the western Pearl River Mouth Basin, the influences of all of these factors have been considered in reaching a conclusion. Carbon isotopes of n-alkanes in the crude oils, and the extracts of the two effective source rocks (the Wenchang and Enping formations) in the basin, exhibit clear differences. The Wenchang source rocks have heavy δ 13 C values that remain almost constant or become slightly heavier with increasing carbon number. The Enping source rocks have light δ 13 C values that become lighter with increasing carbon number. Two groups of oils in this area were identified based on the carbon isotopes of the n-alkanes; groupIoils are similar to extracts of the Wenchang source rocks. However, the groupIIoils are different from both the Wenchang and Enping source rocks and the carbon isotopic profiles of their n-alkanes exhibit a "V" feature with increasing carbon number. The results of artificial thermal maturation experiments indicate that, from the early stage to the peak stage of oil generation (with EasyRo between 0.64% and 1.02%), the δ 13 C values of n-alkanes in the pyrolysis oils become heavier by about 3‰ with increasing thermal maturity, but the shape of the carbon isotopic profiles are not significantly changed. Calculated δ 13 C values of n-alkanes in "mixed" artificial pyrolysis oils indicate that the mixture of oils generated from the same source rocks with different maturities could not change the carbon isotopic profile of the n-alkanes, however, a mixing of the Wenchang and Enping oils could give the "V" feature in the profiles, similar to the groupIIoils in this area. The groupIIoils appear to be mixed Wenchang and Enping oils, the latter being the dominant component in the mixture. We conclude that the source organic matter and the degree of mixing are the main factors controlling the carbon isotopic characteristics of n-alkanes in crude oils in the western Pearl River Mouth Basin. Highlights: The WC and EP formations have different carbon isotopic characteristics of n-alkanes. Mixtures of oils with different sources change carbon isotopic profiles of n-alkanes. GroupIIoils are mixtures of Wenchang and Enping oils.